2011
DOI: 10.1007/s11356-011-0483-7
|View full text |Cite
|
Sign up to set email alerts
|

Some heterocyclic aromatic compounds are Ah receptor agonists in the DR-CALUX assay and the EROD assay with RTL-W1 cells

Abstract: The REP values were comparable to those of larger polycyclic aromatic hydrocarbons, e.g., fluoranthene and pyrene. Thus, and because of the ubiquitous distribution of heterocyclic aromatic compounds in the environment, the provided data will further facilitate the bioanalytical and analytical characterization of environmental samples towards these toxicants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Higley et al (2012) found primarily PAHs, nitro-PAHs, dinitro-PAHs, sterols and naphthoic acids to be associated with ecotoxicological impacts of sediment extracts from the Danube River, whereas PCBs and several other organic pollutants could be excluded. Further, some heterocyclic PAHs (NSO-Het) are also known EROD inducing AhR agonists (Hinger et al, 2011) and -although more water soluble than PAHs -to be among the major CYP1A inducing compounds in sediment from a site strongly contaminated by chemical industry at Bitterfeld, Germany (Brack and Schirmer, 2003). Therefore, the discrepancies between bioTEQs and chem-TEQs can be referred most likely to differences in specific induction potentials, as well as undetected organic and inorganic nontarget compounds with their individual influences on the total TEQs.…”
Section: Responsible Compounds and Potential Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Higley et al (2012) found primarily PAHs, nitro-PAHs, dinitro-PAHs, sterols and naphthoic acids to be associated with ecotoxicological impacts of sediment extracts from the Danube River, whereas PCBs and several other organic pollutants could be excluded. Further, some heterocyclic PAHs (NSO-Het) are also known EROD inducing AhR agonists (Hinger et al, 2011) and -although more water soluble than PAHs -to be among the major CYP1A inducing compounds in sediment from a site strongly contaminated by chemical industry at Bitterfeld, Germany (Brack and Schirmer, 2003). Therefore, the discrepancies between bioTEQs and chem-TEQs can be referred most likely to differences in specific induction potentials, as well as undetected organic and inorganic nontarget compounds with their individual influences on the total TEQs.…”
Section: Responsible Compounds and Potential Sourcesmentioning
confidence: 99%
“…Further, heterocyclic PAHs source from creosote contaminated industrial sites and several have been shown to be AhR agonists and EROD inducers. In addition, they are more bioavailable than their unsubstituted PAHs due to their higher water solubility (Blum et al, 2011;Brinkmann et al, 2014;Hinger et al, 2011).…”
Section: Induction Of Hepatic Erod and Gst Activities In P Vachelliimentioning
confidence: 99%
“…This is becoming of increasing concern in many catchment areas in Europe because sediment contamination often results in a failure to meet the water quality criteria developed by the European Water Framework Directive (Hollert et al, 2007). Persistent organic pollutants (POPs), including polychlorinated dibenzo-pdioxins (PCDDs) and dibenzofurans (PCDFs), polychlorinated biphenyls (PCBs, Koh et al, 2004), halogenated hydrocarbons (HAHs, Villeneuve et al, 2001), as well as polycyclic and heterocyclic aromatic hydrocarbons (PAHs) (Hinger et al, 2011;Villeneuve et al, 2000) are of particular concern in this context because these compounds are found at elevated concentrations in the sediments of virtually every fluvial system with industrial background throughout Europe. Many POPs, particularly those with dioxin-like properties, can bioaccumulate, show great persistence under certain environmental conditions, and are toxic to organisms (Birnbaum and DeVito, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The results were consistent with those of other studies performed previously. Some non-priority PAHs and more polar compounds, such as heterocyclic compounds containing nitrogen, sulfur, or oxygen heteroatoms (NSO-Het), also show dioxin-like activity [50]. The highest AhR agonistic effect of the SPM collected during a flood event from the rivers Neckar and Rhine was found in fractions containing high molecular weight PAHs with more than 16 aromatic C-atoms [51].…”
Section: Resultsmentioning
confidence: 99%